Pemilihan Bahasa sebagai Representasi Identitas Sosial Masyarakat Sulawesi Selatan Pada Interaksi Sosial dalam Perspektif Sosiolinguistik - Indramini Indramini (Journal of Humanities, Social Sciences, and Education, 2026)
This study aims to describe language choice as a representation of the social identity of South Sulawesi society from a sociolinguistic perspective. The research employed a qualitative approach with a descriptive design. Data were collected through participant observation and in-depth interviews with speakers of Bugis, Makassarese, and Indonesian in several areas of South Sulawesi. Purposive sampling was used to determine informants considered relevant to the research focus. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using a sociolinguistic approach. The findings revealed that the people of South Sulawesi actively use more than one language in their daily social interactions. Indonesian is predominantly used in formal contexts such as education and administration, while Bugis and Makassarese are more frequently used in informal interactions that reflect social closeness and cultural identity. The study also found that code-switching and code-mixing occur actively in educational, economic, family, and social media contexts as communication strategies to clarify messages, build intimacy, and adjust to interlocutors. In addition, the development of digital technology has influenced language use patterns, particularly among younger generations who use mixed languages as expressions of digital social identity. Therefore, language functions not only as a communication tool but also as a dynamic representation of social identity in the multilingual society of South Sulawesi.